Immunosuppression - He, Xuehui (IntechOpen, 2020)
Our immune system is equipped with a series of defence mechanisms to recognise and respond to non-self molecules. Although essential for fighting off infections and preventing cancers, destructive immune responses pose a considerable challenge in autoinflammation and transplantation. Currently available immunosuppressants help to control destructive immune responses. However, management of side-effects of lifelong immunosuppression, including cancer development and reduced survival, remain major problems. For this reason, an increasing amount of interest is directed towards the natural specific regulatory mechanism of the immune system. A better understanding of these mechanisms holds the key. This book presents a comprehensive overview of immune suppression in transplantation, cancer and viral infections. Chapters cover modulation of Treg as well as the new era of immunotherapy.